Psychologia jako niezbędny komponent politologii - Baluch, Michał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
Ryszard Skarzynski thinks that the main subject of recognition in political science have to be “the political”, which is constructed by a specific kind of group. Contrary to this opinion R. E. Lane said that political science should be freed-up by political psychology. This kind of group (“political”) is endangered by the roles played by individuals. Sociometry is a solution which helped to measure and explore the phase in which the group is. Personality is also important, because there are some characteristics which can threaten the whole group or the group’s purposes (to stay “political” and not to become “social”). “Delta” questionnaire, EPQ-R, MACH IV should help the group and also political scientists to carry out the research what kind of individuals are members of the group. If political psychology has the best ways to explore this matter, political scientist should use them to distinguish “political” from “others”.